PENGARUH KUALITAS JASA TERHADAP KEPUASAN KONSUMEN PADA KOLAM RENANG OBYEK WISATA PACET MINI PARK - WIDJAYANTI, RINDA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
In a tourism services company, the costomer is important because a company without the consumer is nothing. In providing a service, it is suggested that the service providers prioritize excellence that will be a characteristic of the product that could ultimately achieve customer satisfaction. The purpose of this study is to determine (1) The effect of service quality dimension consisting of tangibles, reliability, responsiveness, assurance, and empathy together (simultaneously) to consumer satisfaction of Pacet travel Mini Park Swimmingpool, (2) the dominant dimension of service quality influence on customer satisfaction of Pacet Mini Park Swimmingpool, with variable dependent is customer satisfaction (Y), and variable independent are tangibles (X1), reliability (X2), responsiveess (X3), assurance (X4), empathy (X5). Loading technique used Non Probability Sampling. Methods of sampling techniques used Accidental Sampling, with 200 respondent sample, and use multiple regression analysis tool ini linier doubled to rescue fund software SPSS 16.0 for windows. Result of the study showed that adjusted R-square value of 60.1% and most dominant variable is the variable assurance with a standardized coefficient 40.3 %. Keywords: Service Quality, Customer Satisfaction